Diesel Particulate Matter Distribution of DI Diesel Engine Using Tire Disposal Fuel - Agung Sudrajad (Bandar Lampung University (UBL), 2012)
Investigation on size distribution of Diesel Particulate Matter (DPM) of DI diesel engine running on tire disposal fuel was observed. The experimental project is comparison of size distribution of DPM between using tire disposal fuel and base diesel fuel. The engine experiment was conducted with YANMAR TF120M single cylinder four stroke diesel engine set-up at variable engine speed at 2400, 2100, 1800, 1500 and 1200 rpm. The data have been taken at each point of engine speed during the stabilized engine-operating regime. Measurement of size distribution of PM at different engine speed conditions have generally indicated bigger for tire disposal fuel compares to base diesel fuel.Â